Indonesia’s Job Loss Insurance Program (JKP): Evaluating Challenges and Opportunities for Worker Welfare and Market Integration - Muhyiddin; Andy Fefta Wijaya; Fadillah Putra; Wike (The Journal of Indonesia Sustainable Development Planning)
The Job Loss Insurance Program (Jaminan Kehilangan Pekerjaan - JKP) was introduced in Indonesia to support workers laid off due to economic downturns by providing financial assistance, reskilling opportunities, and job placement services. This study evaluates the effectiveness of JKP in supporting unemployed workers and identifies key challenges in its implementation. A qualitative approach was employed, combining surveys, semi-structured interviews, focus group discussions, and secondary data from Satu Data Ketenagakerjaan and BPJS Ketenagakerjaan. The findings reveal that while financial assistance was appreciated, it often fell short of covering living expenses, particularly in urban areas. The SIAPKerja platform was underutilized due to irrelevant job postings and low digital literacy among participants. Reskilling programs lacked alignment with labor market demands, limiting their impact on reemployment prospects. Administrative inefficiencies, including delays in benefit disbursement, further hindered the program's success. The study underscores the need for policy reforms to improve JKP’s effectiveness. Recommended measures include aligning training programs with labor market demands, simplifying administrative processes, and enhancing outreach efforts. These changes are essential to ensuring JKP’s role in improving worker welfare and facilitating reintegration into the labor market.